Differentiation tracing identifies hematopoietic regeneration from multipotent progenitors but not stem cells - Nizharadze, Tamar; Busch, Katrin; Fanti, Ann-Kathrin; Rodewald, Hans-Reimer; Höfer, Thomas (Cells & development, 2023)
Hematopoietic stem cells (HSCs) and multipotent progenitors (MPPs) generate the immune system in development, and contribute to its maintenance under steady-state conditions. How stem and progenitor cells respond to increased demand for mature cells upon injury is a fundamental question of stem cell biology. Several studies of murine hematopoiesis have reported increased proliferation of HSCs in situ when exposed to inflammatory stimuli, which has been taken as a proxy for increased HSC differentiation. Such surplus generation of HSC may fuel enhanced HSC differentiation or, alternatively, maintain HSC cellularity in the face of increased cell death without enhanced HSC differentiation. This key question calls for direct measurements of HSC differentiation in their natural niches in vivo. Here, we review work that quantifies native HSC differentiation by fate mapping and mathematical inference. Recent differentiation tracing studies show that HSC do not increase their differentiation rate upon a wide range of challenges, including systemic bacterial infection (sepsis), blood loss, and transient or persistent ablation of specific mature immune cells. By contrast, MPPs differentiate more rapidly in response to systemic infection to accelerate the production of myeloid cells. These new in vivo data identify MPPs as a major source of hematopoietic regeneration; HSCs might not contribute to regeneration while remaining protected.